Gender differences in financial literacy among teenagers - Can confidence bridge the gap? - Justus Blaschke (Cogent Economics & Finance, 2022)
This paper investigates the moderating effect of confidence on the gender gap in financial literacy based on a nationwide survey of German high school students. Two measures of confidence are applied while controlling for cognitive abilities and several independent variables. This study shows that confidence is indeed a strong force in bridging the gender gap, especially for everyday financial concepts. However, significant sex differences persist for more sophisticated financial literacy tasks when confidence variables are introduced in the regression models. Moreover, this paper indicates a significant confidence gap between male and female participants and finds that explanatory characteristics of confidence vary with gender as well. Expertise in the form of increased mathematical abilities and economic education is suggested as a promising confidence-building measure for women. The results suggest that differentiating financial literacy into basic and sophisticated literacy greatly increases interpretability when studying gender differences. Furthermore, the findings have important practical implications for understanding and, thus, closing the gender gap in financial literacy and highlight the political need for financial education in early stages of life that combines theoretical knowledge with confidence building measures.
Keywords: D14; G53; I21; J16; 330; cognitive abilities; confidence; Financial Literacy; gender differences; self-perceived financial literacy